Brazing continuous carbon fiber reinforced Li2O–Al2O3–SiO2 ceramic matrix composites to Ti–6Al–4V alloy using Ag–Cu–Ti active filler metal. (15th December 2015) - Liu, D.; Niu, H.W.; Zhou, Y.H.; Song, X.G.; Tang, D.Y.; Feng, J.C.
Abstract: Cf /LAS composites and TC4 alloy were brazed successfully by vacuum brazing using Ag–Cu–Ti active filler metal. The interfacial microstructure was characterized by a scanning electron microscope, energy dispersive spectrometer and X-ray diffraction. The effects of brazing temperature on the interfacial microstructure and joint properties were investigated in details. Various phases including TiC, TiSi2, Ti3 Cu4, Cu (s, s), Ag (s, s), TiCu and Ti2 Cu were formed in the brazed joints. Interfacial microstructure varies greatly with the increase of brazing temperature, while the amount of Ti2 Cu reduced, but no new phase is generated. The optimal shear strength of the joint is 26.4 MPa when brazed at 890 °C for 10 min. Shear test indicated that the fracture of the brazed joints went through the TiSi2 + TiC layer close to the Cf /LAS composites interface. Graphical abstract: Brazing of continuous carbon fiber reinforced Li2 O–Al2 O3 –SiO2 ceramic matrix composites (Cf /LAS composites) to Ti–6A1–4V (TC4) alloy was achieved with AgCuTi filler metal. (a) The microstructures of Cf /LAS composites. (b) Interfacial microstructure of TC4/AgCuTi/Cf /LAS composites joint brazed at 890 °C for 10 min. (c) Interfacial microstructure of carbon fiber/AgCuTi interface of TC4/AgCuTi/carbon fiber joint brazed at 890 °C for 10 min. (d) Effect of brazing temperature on the shear strength of TC4/AgCuTi/Cf /LAS composites joints. Highlights: Continuous carbon fiber reinforced Li2 O–Al2 O3 –SiO2 composites was successfully brazed. Interfacial microstructure and joint properties depended on brazing temperature. The highest shear strength of joints reached 26.4 MPa.